Hybrid peptides inspired by the RWQWRWQWR sequence inhibit cervical cancer cells growth in vitro - Natalia Ardila-Chantré; Claudia Marcela Parra-Giraldo; Yerly Vargas-Casanova; Andrea Carolina Barragán-Cardenas; Ricardo Fierro-Medina; Zuly Jenny Rivera-Monroy; Jhon Erick Rivera-Monroy; Javier Eduardo García-Castañeda (Exploration of Drug Science)
Aim: The aim of this research was to generate new peptide molecules with cytotoxic activity against cervical cancer that can become effective in mitigating the impact of the disease and preventing its progression. The design is based on the hybrid peptide formation strategy that allows new chemical entities to be obtained from the union of fragments of different bioactive peptides. Specifically, we worked by combining the RWQWRWQWR sequence derived from bovine lactoferricin with different functional peptides such as anticancer peptides, cervical cancer cell-targeting peptides, and cell-penetrating peptides. Methods: Hybrid peptides and precursors were synthesized by solid-phase peptide synthesis using the Fmoc/tBu strategy, purified via reverse phase (RP)-solid phase extraction, and characterized by RP-high performance liquid chromatography (RP-HPLC) chromatography and mass spectrometry. In vitro cytotoxicity of hybrid peptides in human cervical cancer cells lines HeLa and Ca Ski was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Results: All hybrid peptides were obtained with high purity and the experimental mass corresponds with the theoretical mass. Some hybrid peptides exhibited significant, fast, and selective cytotoxic activity against the cancerous cells evaluated, specifically those containing sequences of anticancer peptides and cell-penetrating peptides. The cytotoxic effect exerted by the monomeric and dimeric hybrid peptides depended on the concentration of the peptide, which allowed the determination of the IC50 values and the selectivity index (SI). Conclusions: We obtained hybrid peptides with the core sequence RWQWRWQWR that are active against HeLa and Ca Ski cell lines. The combination of the RWQWRWQWR sequence with short anticancer peptides and cell-penetrating peptides allowed the creation of hybrid peptides with improved cytotoxic potency against cervical cancer. Hybrid peptides constitute a novel, viable, and useful strategy for the design and identification of peptide drugs with anticancer activity.